2018
DOI: 10.21276/ijcmr.2018.5.6.16
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Steroid Injection in the Management of Patients with Subacute or Chronic Low Back Ache with Radiculopathy due to Herniated Disc

Abstract: Introduction: Low back ache is the most common problem seen in orthopedic clinic. Low backache with lumbosacral radiculopathy remains the most challenging musculoskeletal problem for its therapeutic management. In around 90% patients, the cause of low back with radiculopathy is a prolapsed disc. Epidural steroid injections are used in the management of patients with subacute or chronic low backache with radiculopathy, not responding to conservative treatment. The aim of study was to check the efficacy of epidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…All of these events were mild and transient and subsided with conservative therapy. These observations is agree with other studies carried out by Madhukar et al, Gul et al and Runu et al 16,24,25 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…All of these events were mild and transient and subsided with conservative therapy. These observations is agree with other studies carried out by Madhukar et al, Gul et al and Runu et al 16,24,25 .…”
Section: Discussionsupporting
confidence: 94%
“…So that, ECI provides analgesia for a variable duration during which the patient be able to practice rehabilitation exercises 23 . Methyl prednisolone was used in this study for its anti-inflammatory effects and for its long acting duration 24 . Moreover, it was found that the existence of methyl prednisolone in epidural gap suppresses transmission in unmyelinated C fibres, the major nociceptive pathway 25 .…”
Section: Discussionmentioning
confidence: 99%